Upgrading no cluster de rochas ornamentais do Espírito Santo, Brasil - Lennan, Maria Laura Ferranty Mac (2012)
This work verifies the effects of governance of value chains upgrading of enterprises in the cluster of ornamental Espírito Santo, Brazil. The quantitative methodology was used to achieve the proposed objectives and respond to the research question. More specifically we conducted a survey of 32 companies affiliated to the Centre Rocks, located in the regions of Itapemirim and saws, Holy Spirit. Data were analyzed using parametric and non-parametric statistical techniques, given the type of sample distribution. The results indicate that firms in the cluster are embedded in value chains governance market type, the export performance has no direct relationship with the percentage exported and finally the upgrading of enterprises and their marketing investments impacting on the competitiveness of their sales to the foreign market.